2019
DOI: 10.1038/s41467-019-10877-8
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-region exome sequencing reveals genomic evolution from preneoplasia to lung adenocarcinoma

Abstract: There has been a dramatic increase in the detection of lung nodules, many of which are preneoplasia atypical adenomatous hyperplasia (AAH), adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA) or invasive adenocarcinoma (ADC). The molecular landscape and the evolutionary trajectory of lung preneoplasia have not been well defined. Here, we perform multi-region exome sequencing of 116 resected lung nodules including AAH (n = 22), AIS (n = 27), MIA (n = 54) and synchronous ADC (n = 13). Comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
123
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 46 publications
9
123
1
Order By: Relevance
“…4A). Genomic analysis of the same cohort of IPNs in our previous study have revealed progressive increase in mutation burden from AAH to ADC, while SCNA only became obvious after stage of AIS and AI events were rare in AAH and AIS 7 .…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…4A). Genomic analysis of the same cohort of IPNs in our previous study have revealed progressive increase in mutation burden from AAH to ADC, while SCNA only became obvious after stage of AIS and AI events were rare in AAH and AIS 7 .…”
Section: Discussionmentioning
confidence: 59%
“…29 lung nodules from 15 patients had multiregional specimens for spatial heterogeneity assessment (Supplementary Table 1). Wholeexome sequencing (WES) data was available for all specimens (EGAS00001004960) 7 .…”
Section: Sample Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical advances in lung cancer screening as well as its expanded implementation have allowed the detection of what was termed as indeterminate pulmonary nodules (IPNs), as well as brought forth the potential of investigating these resected nodules in novel and unique cohorts. IPNs of the lung were found to be histologically elusive, classifying as AAH, adenoma in situ (AIS), minimally invasive adenoma (MIA), or even invasive LUAD (265). Using multi-region exome sequencing, researchers investigated the evolutionary trajectory of those IPNs, revealing evidence for a progressive genomic evolution from AAH to AIS, MIA, and LUADs, as well as a selective evolutionary model characterized by the outgrowth of fit subclones and sweep of unfit subclones, during initiation and early progression of lung preneoplasia (265).…”
Section: Immunogenomics For a Deeper Understanding Of Pmlsmentioning
confidence: 99%
“…IPNs of the lung were found to be histologically elusive, classifying as AAH, adenoma in situ (AIS), minimally invasive adenoma (MIA), or even invasive LUAD (265). Using multi-region exome sequencing, researchers investigated the evolutionary trajectory of those IPNs, revealing evidence for a progressive genomic evolution from AAH to AIS, MIA, and LUADs, as well as a selective evolutionary model characterized by the outgrowth of fit subclones and sweep of unfit subclones, during initiation and early progression of lung preneoplasia (265). Further analysis of neoantigens in this dataset may provide valuable insights into the concurrent evolution of the immunogneomic landscape mirroring the progression of PMLs into LUADs.…”
Section: Immunogenomics For a Deeper Understanding Of Pmlsmentioning
confidence: 99%